Climate crisis economics : a race of tipping points - Mackintosh, Stuart P. M. (Routledge, 2025)
"Climate Crisis Economics draws on economics, political economy, scientific literature, and data to gauge the extent to which our various communities - political, economic, business - are making the essential leap to a new narrative and policy approach that will accelerate us towards the necessary transition to a decarbonized economy and sustainable future. The book draws out policies and practices with both national and local examples, which demonstrate various complementary approaches that are empowering states and people as they seek to pursue the carbon neutral goal. The author delineates a climate crisis economics approach that is fit for purpose and which can help achieve necessary climate change goals in the decades ahead. This new 2nd edition has been thoroughly updated throughout, including new material on the Biden administration and countries outside the USA and Europe; new chapters on green finance and a just transition; and key questions and supplemental reading for each chapter. Written in an accessible voice, Climate Crisis Economics draws on work in fields outside of and in addition to politics and economics to make a case for climate crisis economics as an approach to addressing the climate change challenge ahead. It will appeal to academics, students, investors, and professionals from varying disciplines including politics, international political economy, and international economics"-- Provided by publisher.
Keywords: Climatic changes -- Economic aspects.; Climatic changes -- Political aspects.; Climate change mitigation -- Government policy.; elektronické knihy; electronic books